Infertility in 1 Samuel 1:9–20 and Luke 1:5–25: Cultural and spiritual lessons for amaXhosa - Mlamli Diko (HTS Teologiese Studies/Theological Studies)
Infertility within amaXhosa, as in 1 Samuel 1:9–20 and Luke 1:5–25, bears a significant cultural stigma and is associated with ancestral and spiritual interpretations. In this article, I unmask the challenges of infertility in these two biblical scriptures through ancestralism and African spirituality as theoretical frameworks. In so doing, I concentrate on the cultural and spiritual lessons these biblical scriptures may offer to amaXhosa in contemporary contexts and beyond. This article made two notable findings. Firstly, the biblical experiences of Hannah and Elizabeth underscore how spiritual intercession and perseverance are fundamental in overcoming the challenges and destructive stigmas associated with infertility, which is directly echoed in the amaXhosa culture’s reliance on ancestral intervention, spiritual guidance, offerings and rituals. Secondly, blending ancestral and African spirituality with contemporary medical techniques may create a more holistic window for addressing infertility within amaXhosa, where cultural heritage and modern resources coexist. Therefore, these findings draw on both the spiritual dimensions in the selected biblical texts and cultural parallels in amaXhosa traditions and customs, aiming to bridge ancient and contemporary understandings of infertility.